Fluid Genetic Analyses Predict the Biological Behavior of Pancreatic Cysts: Three-year Experience - Kung, Jonathan S; Lopez, Oscar A; McCoy, Erin E; Reicher, Sofiya; Eysselein, Viktor E (JOP. Journal of the Pancreas, 2014)
Context EUS with fine-needle aspiration and cyst fluid analysis is routinely used to evaluate pancreatic cysts; however, the clinical course of these lesions is often not well defined. Objective Our study evaluated whether EUS imaging, cyst fluid CEA, and cytology combined with cyst fluid genetic analyses for allelic imbalance and genetic mutations can be used to better predict the malignant potential of pancreatic cysts. Patients Seventy-two patients underwent EUS-FNA for evaluation of pancreatic cysts from 2010 to 2013. Design In addition to routine cytology and fluid CEA, the aspirated cyst fluid was analyzed for the presence of KRAS mutations, GNAS mutations, and allelic imbalance (loss of heterozygosity). Patients were followed up to 3 years. Setting Tertiary care center. Results EUS revealed 39 IPMNs, 17 mucinous cystic neoplasms, and 16 serous cystadenomas. Twenty two of 56 patients with IPMNs or mucinous cystic neoplasms had pancreatic cysts with abnormal genetic fluid analysis. Of those 22 patients, 18 contained a non-benign clinical diagnosis. This is consistent with cyst fluid genetic analysis carrying a sensitivity and specificity of 75% and 88%, respectively, and a positive predictive value of 82%.There was also a significant negative predictive value of 81%. For mucinous cystic neoplasms the negative predictive value was 100%. Conclusion Genetic mutations and allelic imbalance detected in pancreatic mucinous cysts are associated with progression to malignancy and could be helpful as predictors of biological behavior of pancreatic cysts. In our experience, genetic analyses when used in combination with EUS imaging, cytology, and fluid CEA could serve as a guide to clinical decisions regarding cyst surgical resection and follow up. Image: Pancreatic cysts: flow chart.